A Unique Radiation Scheme for the Treatment of High-Grade Non-Metastatic Soft Tissue Sarcoma: The Detroit Medical Center Experience. (2005) - Fontanesi, James; Mott, Michael P.; Kraut, Michael J.; Lucas, David R.; Miller, Peter R.
Abstract : Purpose: This is the initial report on the utilization of combined photon irradiation followed by a neutron boost irradiation for the initial management of patients with high-grade non-metastatic soft tissue sarcoma (STS). We present data on local control, complications, disease-free survival and overall survival in patients at high risk for local relapse. Methods and materials: Between 1/1/1995 and 10/31/02, twenty-three patients with high-grade non-metastatic soft tissue sarcoma were referred to the Department of Radiation Oncology at the Detroit Medical Center. These patients were referred for consultation due to surgical margin status (tumor within 3mm of surgical margin ( n =11)), or gross residual disease ( n =12). There were 14 males and nine females whose ages ranged from 12 to 75 at the time of diagnosis (med=44 years). The most common histology was malignant fibrous histiocytoma ( n =6), followed by liposarcoma ( n =5), synovial sarcoma ( n =4), and angiosarcoma ( n =2). Twenty-one of 23 patients also received multi-agent multi-cyclic cyto-reductive therapy. Treatment consisted of initial daily photon irradiation delivered either using twice daily fractions of 120 cGy ( n =10) or once daily 200 cGy/fx ( n =13).Total photon dose was 36–39.6 Gy. Neutron irradiation was initiated immediately following the photon irradiation and consisted of fraction sizes of 1.0–1.25NGy to a total dose of 6–10 NGy. The neutrons were given once daily. Follow-up is calculated from the day of last radiation treatment. Results: No patient has been lost to follow-up, which has ranged from 18 to 82 months (med=36 months). To date there have been two local relapses and three patients with distant disease development without local relapse. Each of the patients with distant disease has died. The local failures occurred at 9 and 12 months. The 36-month local control is 91%. Thirtysix month disease-free survival was 78%. Overall survival at 36 months was 87%. Three patients had unusual complications consisting of delayed wound healing, and in one of these patients a fracture of the tibia has been noted. Conclusion: The use of this unique radiation sequence post-surgically in patients at high risk for local relapse has resulted in an exciting 36-month local control rate of 91%. The 3-year disease-free survival of 78% and overall survival rate of 87% are exciting but need to mature. The low complication rate is similar to that reported in other large institutional series that have not utilized neutrons. We continue to evaluate the role of combined photon and once-off neutron irradiation in the treatment of patients with high-grade STS that are risk for local recurrence.